International collaboration of early-stage researchers in nursing science: A discussion paper - Inkeroinen, Saija (Sage, 2025)
Nursing is a global profession and international collaboration of early-stage researchers (ESRs) builds their capacity as future nursing scientists. This discussion paper focuses on international collaboration of ESRs in nursing science. The aim of this paper was to clarify the optimal collaboration forms and identify challenges and recommendations for supporting individual researchers and organisations to strengthen international collaboration for the ESR phase. The paper is based on previous literature and authors’ experiences in the collaboration between two countries by the Baltic Sea, Estonia and Finland. In future, more discussion is needed on how to establish international partnerships and collaboration in researcher career building globally: expanded and long-term collaboration is needed to develop nursing science but also to improve nursing care, patient outcomes and, finally, to benefit society.